Pengelolaan Limbah Bahan Berbahaya dan Beracun Ditinjau Dari Aspek Hubungan Industrial dan Corporate Social Responsibility - Ulima Harma; Timbul Dompak (Dialektika Publik, 2020)
The purpose of this research to see how management Hazardous and Toxic Material Waste Judging From the Aspects of Industrial Relations and Corporate Social Responsibility. This type of research used in this research is descriptive research with a qualitative approach. The results of this study show that the management of Hazardous and Toxic Material Waste Judging from the aspects of industrial relations and corporate social responsibility, although there are still some shortcomings. Such as that there are still many industrial companies that are not very aggressive in carrying out the B3 waste management process. This proves that the policies governing waste management have not been so effectively applied in life, this can be caused by several factors such as lack of awareness in managing B3 waste, a less strict supervision system, and also rules that are felt to be not too binding so that many do not manage B3 waste properly.